Global supply chains in the pharmaceutical industry - Nozari, Hamed, 1984-; Szmelter, Agnieszka, 1989- (Business Science Reference, 2019)
"This book presents a complex view of supply chain management in global pharmaceutical industry, theory and empirical research findings. It also provides the resources necessary for policy makers and managers to adopt and implement supply chain in developing nations across the globe"--